Scaphoidectomy and Capsulodesis for SNAC or SLAC Stage II - Trumble, Thomas E.; Rafijah, Gregory; Alexander, Hayley; Waitayawinyu, Thanapong (Journal of Wrist Surgery, 2012)
Two common types of wrist arthritis are scapholunate advanced collapse (SLAC) and scaphoid nonunion advanced collapse (SNAC). In stage II SLAC or SNAC, there is arthritis between the scaphoid and the radius, sparing the cartilage between the capitate and the lunate and between the lunate and the radius. When nonsurgical treatment failed, scaphoidectomy plus capsulorrhaphy was used in 8 patients to provide pain relief without requiring an arthrodesis or compromising the radiolunate articulation. After surgery the pain scores improved from 8.5 preoperatively to 2.4 postoperatively. The Disabilities of the Arm, Shoulder, and Hand (DASH) score averaged 21, and the grip strength improved from 18 to 28 kg (81% of the contralateral side).
Keywords: scapholunate advanced collapse (SLAC) arthritis; scaphoid nonunion advanced collapse (SNAC) arthritis; wrist arthritis; scaphoid nonunion; capsulorrhaphy